Priority actions for Fusarium head blight resistance in durum wheat: Insights from the wheat initiative - Viviani, Ambra; Haile, Jemanesh K.; Fernando, Wannakuwattewaduge Gerard Dilantha; Ceoloni, Carla; Kuzmanović, Ljiljana; Lhamo, Dhondup; Gu, Yong Qiang; Xu, Steven; Cai, Xiwen; Buerstmayr, Hermann; Elias, Elias M.; Confortini, Alessia; et al. (John Wiley & Sons, 2025)
Fusarium head blight (FHB), mainly caused by Fusarium graminearum and Fusarium culmorum, is a major wheat disease. Significant efforts have been made to improve resistance to FHB in bread wheat (Triticum aestivum), but more work is needed for durum wheat (Triticum turgidum spp. durum). Bread wheat has ample genetic variation for resistance breeding, which can be readily exploited, while durum wheat is characterized by higher disease susceptibility and fewer valuable resistance sources. The Wheat Initiative - Expert Working Group on Durum Wheat Genomics and Breeding has promoted a scientific discussion to define the key actions that should be prioritized for achieving resistance in durum wheat comparable to that found in bread wheat. Here, a detailed state of the art and novel tools to improve FHB resistance in durum are presented, together with a perspective on the next steps forward. A meta-analysis grouping all quantitative trait loci (QTL) associated with FHB resistance in both bread and durum wheat has been conducted to identify hotspot regions that do not overlap with Rht alleles, which are known to negatively correlate with FHB resistance. A detailed list of QTL related to FHB resistance and deoxynivalenol contamination and durum lines carrying different sources of FHB resistance are provided as a strategic resource. QTL, closely linked markers and durum wheat lines carrying the useful alleles, can be selected to design an effective breeding program. Finally, we highlight the priority actions that should be implemented to achieve satisfactory resistance to FHB in durum wheat.